Grievance Arbitration of Discharge Cases, A Study of the Concept of Industrial Dsicipline and their Result - Roy, André (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Grievance Arbitration of Discharge Cases, A Study of the Concept of Industrial Dsicipline and their Result," by George W. Adams.